2015
DOI: 10.3349/ymj.2015.56.6.1735
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Planning by 3D Printing for Primary Cardiac Schwannoma Resection

Abstract: We report herein a case of benign cardiac schwannoma in the interatrial septum. A 42-year-old woman was transferred from a clinic because of cardiomegaly as determined by chest X-ray. A transthoracic echocardiography and chest computed tomography examination revealed a huge mass in the pericardium compressing the right atrium, superior vena cava (SVC), left atrium, and superior pulmonary vein. To confirm that the tumor originated from either heart or mediastinum, cine magnetic resonance imaging was performed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 4 publications
0
33
0
1
Order By: Relevance
“…3D TTE/TEE Left atrial appendage occlusion [14], postoperative hemodynamic testing following MitraClip procedure [41] MRI TGA, VSD, PS [42], DORV [43], hypoplastic aortic arch [44], aortic arch aneurysm [45], pulmonary atresia, ASD, tricuspid regurgitation, dextrocardia [46], retroesophageal LSA + right aortic arch [47] MSCT ASD [48,49], VSD [50], LAA occlusion [51], severe AS [52], extensive AA [53], severe mitral valve regurgitation [54], neopulmonary stenosis [55], primary dilated cardiomyopathy [56], primary cardiac schwannoma [57], double-chambered right ventricle [58], severe pulmonary venous stenosis [59], complex aortic obstruction [60], juxtarenal AA [61], DOLV, VSD, PS [62], left atrium osteosarcoma [63], hypertrophic cardiomyopathy [64], prosthetic MV perivalvular leak [65], ventricular aneurysm [66], pulmonary venous baffle to the systemic right ventricle [67], tricuspid atresia [67], His bundle pacing [68] AA -atherosclerotic aneurysm; rest abbreviations are the same with the Table 1 www.cardiologyjournal.org three challenges are discussed which need to be addressed in the future.…”
Section: Imaging Techniques Diseasesmentioning
confidence: 99%
“…3D TTE/TEE Left atrial appendage occlusion [14], postoperative hemodynamic testing following MitraClip procedure [41] MRI TGA, VSD, PS [42], DORV [43], hypoplastic aortic arch [44], aortic arch aneurysm [45], pulmonary atresia, ASD, tricuspid regurgitation, dextrocardia [46], retroesophageal LSA + right aortic arch [47] MSCT ASD [48,49], VSD [50], LAA occlusion [51], severe AS [52], extensive AA [53], severe mitral valve regurgitation [54], neopulmonary stenosis [55], primary dilated cardiomyopathy [56], primary cardiac schwannoma [57], double-chambered right ventricle [58], severe pulmonary venous stenosis [59], complex aortic obstruction [60], juxtarenal AA [61], DOLV, VSD, PS [62], left atrium osteosarcoma [63], hypertrophic cardiomyopathy [64], prosthetic MV perivalvular leak [65], ventricular aneurysm [66], pulmonary venous baffle to the systemic right ventricle [67], tricuspid atresia [67], His bundle pacing [68] AA -atherosclerotic aneurysm; rest abbreviations are the same with the Table 1 www.cardiologyjournal.org three challenges are discussed which need to be addressed in the future.…”
Section: Imaging Techniques Diseasesmentioning
confidence: 99%
“…In that study, of 19 surgeons who used a total of 52 models of tumors throughout the body, 94% considered them very helpful for treatment planning, and 71% felt they improved the surgical approach. To our knowledge, 3D‐printed models specific to thoracic tumors have been reported for two patients with Pancoast tumors, a pediatric patient with primary mediastinal synovial sarcoma invading the SVC, a patient with an ectopic mediastinal thymoma, a patient with a pectoralis minor muscle spindle cell neoplasm, and a patient with a cardiac schwannoma . Benefits reported for these cases include better understanding of tumor relationship to surrounding normal tissues, helping to avoid resecting uninvolved structures, and enhancing the likelihood of complete resection.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, 3D-printed models specific to thoracic tumors have been reported for two patients with Pancoast tumors, 5,6 a pediatric patient with primary mediastinal synovial sarcoma invading the SVC, 16 a patient with an 5 and a patient with a cardiac schwannoma. 18 Benefits reported for these cases include better understanding of tumor relationship to surrounding normal tissues, helping to avoid resecting uninvolved structures, and enhancing the likelihood of complete resection. One difficulty in adopting the technology described in all the above studies is that they have used either research 5,16 or engineering-oriented 2,6 3D printing software that is unfamiliar and/or unavailable to most radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the 3D printed model is more instrumental in guiding surgery compared to 2D measurement data. Son et al [7] reported that they successfully performed a primary cardiac schwannoma excision with the guidance of a 3D printed model. The model was adopted because the tumor origin of the patient could not be ascertained by CT, MRI or echocardiography.…”
mentioning
confidence: 99%